THE NETWORK PLATFORM ARCHITECTURE FOR MONITORING OBJECTS IN CYBERPHYSICAL SYSTEMS OF SMART CITIES - DUDA, OLEKSII; STANKO, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Currently, systems supporting the infrastructure of "smart cities", formed on the basis of an extensive list of information and communication technologies, are being actively implemented around the world. Almost any urban object can be a collector, distributor and consumer of information. Cyber-physical or "smart" systems are actively used to ensure the processes of formation of information flows. In the future, these systems will become the basis of critically important urban infrastructure. However, at present, the large-scale implementation of urban cyber-physical systems is accompanied by an extensive list of unsolved problems, and the active development of technologies forms the port of the development of unified information technology models and architectures. The main directions of development of "smart cities" are considered in the work. A "smart cities" cyber-physical systems classification  has been created and the reasons for complicating the creating unique information-technological structures processes for managing these systems have been identified. An analysis of widespread approaches to the information and technological architectures formation for the "smart cities" cyber-physical systems implementation was carried out. The network platform information technology architecture for monitoring "smart cities" cyber-physical objects is proposed, which is based on three infrastructure levels (cyber-physical, network and cloud) for the modern computing paradigms effective integration (edge, fog and cloud). Application of the proposed architecture will ensure extensibility, compatibility, self-consistency and reproducibility when implementing innovative "smart" city services and services based on cyber-physical systems.
Keywords: information technology architecture; data lakes; cyber-physical devices distributed system; smart city services; cloud; fog and edge computing